Determining key factors influencing SMEs' performance: A systematic literature review and experts' verification - Hassan Dauda Yahaya; Gunalan Nadarajah (Cogent Business & Management, 2023)
In today's competitive business environment, SMEs face challenges in strategic orientation, resource allocation, and adapting to market changes due to their limited size and resources, which hinders access to crucial data and insights, affecting decision-making and growth opportunities. Their innovation, learning, and entrepreneurial mindset are vital in achieving sustainable competitive advantage. To ensure their long-term success and growth, targeted government support and tailored strategies prioritising innovation and continuous learning are essential for empowering SMEs to thrive amidst intense competition. By combining these efforts, SMEs can unlock their potential and succeed in the dynamic business landscape. A systematic literature review addressed this gap, developing a comprehensive framework based on Resource Base View and Institutional Theory. The study involved identifying 469 articles from reputable databases and analysing the results using a one-sample T-test. Ultimately, 16 papers were deemed most relevant for building the conceptual framework. The findings indicate that 13 factors significantly impact a firm's strategic orientation and performance in today's knowledge-based and uncertain global business environment. It should be noted that other relevant factors may have been overlooked, and future research should consider a more detailed approach, such as meta-analysis, to broaden the field's knowledge. The established framework establishes a relationship between strategic orientation and firm performance. It was developed by carefully selecting and confirming the most influential factors in SMEs' performance literature using systematic literature review and expert verification methods. This framework has the potential to guide future research and offers valuable insights for firms aiming to enhance their strategic orientation and performance in the competitive business landscape. Overall, this study contributes to the existing body of knowledge by synthesising previous research, providing insights into theoretical and conceptual frameworks, identifying key factors influencing strategic orientation, and highlighting best practices and lessons learned.
Keywords: 650; entrepreneurial orientation; firm performance; innovation capability; learning orientation; market orientation; systematic literature review